Diagenesis of juvenile skeletal remains: A multimodal and multiscale approach to examine the post-mortem decay of children's bones. (November 2021) - Caruso, Valentina; Marinoni, Nicoletta; Diella, Valeria; Possenti, Elena; Mancini, Lucia; Cantaluppi, Marco; Berna, Francesco; Cattaneo, Cristina; Pavese, Alessandro
Abstract: This study aimed to examine the degradation of juvenile skeletal remains with respect to adult counterparts from different burial settings in Milan, Italy. A multiscale and multimodal approach was applied to investigate bone diagenesis by combining chemical and mineralogical analyses with synchrotron radiation-based virtual histology. Certain differences could be observed between child and adult skeletal remains; juvenile bones exhibited ( i ) poorer histological conservation, with prominent general re-organisation of the observed three-dimensional original microstructure, resulting in denser structures with low porosity; ( ii ) bioapatites with low defective structures, with chemical compositions highly site-sensitive, exhibiting variation even within a single bone; ( iii ) organic matter highly variable in terms of quality, quantity, and arrangement, even within a single bone sample. Conversely, organic decay results in similar enrichment in calcium content both in juveniles and in adults. In conclusion, the present work points out high intra-individual skeletal preservation in archaeological juvenile bones with respect to adults, thus suggesting that immature and mature bone tissues deteriorate at different rates, foremost as a function of their intrinsic features (shape, porosity, histological structures, etc.), and secondarily under the influence of the burial environment. Highlights: Children's bones decompose more rapidly than those of adults. The survival of a bone is influenced by its intrinsic features and burial conditions. Composition varies within a single bone or between bones from the same site. Juvenile remains exhibit a lesser fraction of undisturbed microstructure. Immature and mature bone tissues deteriorate at different rates.